Zdrowotne, społeczne i ekonomiczne wymiary jakości usług zdrowotnych: Health, social and economic dimensions of the quality of health services - Grynchutskyi, Valerii; Machuga, Nadiia (Management and Administration Journal, 2021)
The purpose of this article is to discuss issues related to the quality of health servicesevaluations. The analysis covered aspects of the formation of good quality health care. Meterswere considered as a quality of the health services, and the factors that affect the quality of medical services were described. There were also proposed recommendations for the Ukraine regarding the introduction of the quality of health services.